Modelling of validation process with BPMN notation - Joanna Łabędzka (Edukacja Ustawiczna Dorosłych)
The European Union supports measures to ensure the visibility and value of skills acquired through non-formal and informal learning. The validation process helps to bridge the educational inequalities, and offers further pathways for the development of skills and competences needed in life and in the EU labour market. The paper points out the importance of the business process modeling as fundamental for modern systems (education, technology, business etc.) due to the increasing rate of change and uncertainty. As a result, business processes, educational in particular, need to be continuously redesigned and subsequently aligned with the corresponding information systems and customer requirements. Issues related to the Business Process Management (BPM) for validation are also addressed in the paper. BPM focuses on streamlining complex processes to help businesses run smoothly. It was therefore natural to think about using the BPM approach, and also using BPMN as the underlying method for common understanding and presenting the global perspectives on recognising non-formal and informal learning. In the empirical part of the paper, the BPMN model of recognition, validation and certification of competences that aims at creating the coherent system for validation was presented.